2007
DOI: 10.1161/01.res.0000261982.76892.09
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Remodeling in Transplant Vasculopathy

Abstract: Abstract-As therapeutic strategies to prevent acute rejection progressively improve, transplant vasculopathy (TV)constitutes the single most important limitation for long-term functioning of solid organ allografts. In TV, allograft arteries characteristically develop severe, diffuse intimal hyperplastic lesions that eventually compromise luminal flow and cause ischemic graft failure. Traditional immunosuppressive strategies that check acute allograft rejection do not prevent TV; indeed 50% of transplant recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
217
2
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(225 citation statements)
references
References 178 publications
(163 reference statements)
2
217
2
4
Order By: Relevance
“…TV in its full development is characterized by intimal thickening and luminal narrowing of allograft arteries, ultimately leading to acute occlusive events and associated tissue infarction. The pathogenesis of TV involves two main arterial changes: structural changes leading to thickening of the intima and vasomotor dysfunction characterized by defective arterial vasodilation and/or aberrant vasoconstriction (14). Thickening of the arterial intima in TV is caused by immunemediated damage and dysfunction of the graft endothelium, which leads to leukocyte and smooth muscle cell migration into this layer of the vessel wall (15).…”
Section: Ascular Endothelial Cells (Ecs) Regulate Inflammatory Andmentioning
confidence: 99%
“…TV in its full development is characterized by intimal thickening and luminal narrowing of allograft arteries, ultimately leading to acute occlusive events and associated tissue infarction. The pathogenesis of TV involves two main arterial changes: structural changes leading to thickening of the intima and vasomotor dysfunction characterized by defective arterial vasodilation and/or aberrant vasoconstriction (14). Thickening of the arterial intima in TV is caused by immunemediated damage and dysfunction of the graft endothelium, which leads to leukocyte and smooth muscle cell migration into this layer of the vessel wall (15).…”
Section: Ascular Endothelial Cells (Ecs) Regulate Inflammatory Andmentioning
confidence: 99%
“…10,11 The unabated expansion of VSMCs can lead to pathophysiologic complications, such as clinical restenosis after percutaneous coronary intervention, 12,13 arteriovenous shunt failure, 14,15 and transplant vasculopathy. 16 Generally, VSMCs are programmed to avoid this excessive reparative response, because they possess the capacity to sense and respond to extracellular and intracellular cues that trigger the reversion to the contractile phenotype.…”
mentioning
confidence: 99%
“…It has also been demonstrated that C-reactive protein (CRP) and cytokines (such as IL-6 and platelet-activating factor) are associated with arrhythmias through the modulation of ion channel function [11,12] and the aggravation of sympathetic tone [11]. Hence, elevated levels of inflammatory mediators may provoke vasculopathy, myocardial fibrosis, sympathetic hyperactivity and ion channel malfunction [12][13][14][15], which can lead to a high risk of cardiac arrhythmias and even death.…”
mentioning
confidence: 99%